Treatment of hepatitis B virus: an update. (December 2016) - Ward, Haley; Tang, Lydia; Poonia, Bhawna; Kottilil, Shyam
Chronic hepatitis B virus infection is a global health concern as it affects over 240 million people worldwide and an estimated 686, 000 people die annually as a result of complications of the disease. With the development of newer antiviral drugs, viral suppression of HBV is achievable, however elimination of HBV from infected individuals (functional cure) remains an issue. Due to persistence of HBV DNA (cccDNA) in infected cells, chronically infected patients who discontinue therapy prior to HBsAg loss or seroconversion are likely to relapse. Several novel therapeutic strategies are being researched and studied in clinical trials. Here we review these novel strategies to achieve sustained cure or elimination of HBV. These strategies include the targeting of the host or viral factors required for viral persistence as well as therapeutic vaccines.